Efektivitas Pengelolaan BUMDes Sataretanan dalam Meningkatkan Pendapatan Asli Desa - Romaiki Hafni; Affan Affan; M. Naulul Hakiki (AL-Muqayyad, 2021)
The purpose of this article is to determine the management strategy of the Sataretanan BUMDes and to analyze the effectiveness of the Sataretanan BUMDes in increasing Village Original Income. Data collection techniques using observation, interviews, and documentation. The data analysis technique is descriptive analysis. The results of the management strategy research carried out by BUMDes Sataretanan held regular meetings of BUMDes internal members to evaluate the entire development of the BUMDes Management Program, formed business groups from each hamlet that were members of the SDS business group (Soddara Dhelem Sataretanan), held entrepreneurship training and product production assistance. establish cooperation with DPMD, Department of agriculture and plantations, Disperindag and Disnakertrans. The effectiveness of the Sataretanan BUMDes management has not been effective because it has not met all indicators of effectiveness. Of the three indicators that are used as analytical tools, namely goal achievement, integration, and adaptation, only one can be met, namely the integration indicator